2008
DOI: 10.2478/s11532-008-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel organic material with potential NLO application - electronic and spectroscopic properties

Abstract: Novel dicyanoisophorone derivative, (E)-2-(3-(4-aminostyryl)-5,5-dimethylcyclohex-2-enylidene)malononitrile, is synthesized and its structure elucidated by means of conventional and linear polarized IR-spectroscopy of oriented colloids in nematic host, H-COSY NMR, HPLC tandem ESI MS-MS spectrometry, UV-VIS and thermal methods.Ab initio and DFT level of theory are used to theoretically obtain the electronic structure and optical properties, both in ground and exited state, of the compound.© Versita Warsaw and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…On the other hand, using ab initio CIS/HF, Oumi et al [22] studied chalcone and its hydroxyl derivatives, but the differences reported between gas-phase theoretical and solvated experimental λ max are quite large (0.7eV on average). In recent years, time-dependent density functional theory (TD-DFT) has emerged as a reliable standard tool for the theoretical treatment of electronic excitation spectra and recent works demonstrate the good accuracy for a wide range of systems [23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, the computational cost of TD-DFT calculation is comparative to that of a Hartree-Fock based single excitation theory, such as, configuration interaction singles (CIS) or time-dependent Hartree-Fock (TDHF) method.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, using ab initio CIS/HF, Oumi et al [22] studied chalcone and its hydroxyl derivatives, but the differences reported between gas-phase theoretical and solvated experimental λ max are quite large (0.7eV on average). In recent years, time-dependent density functional theory (TD-DFT) has emerged as a reliable standard tool for the theoretical treatment of electronic excitation spectra and recent works demonstrate the good accuracy for a wide range of systems [23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, the computational cost of TD-DFT calculation is comparative to that of a Hartree-Fock based single excitation theory, such as, configuration interaction singles (CIS) or time-dependent Hartree-Fock (TDHF) method.…”
Section: Introductionmentioning
confidence: 99%
“…20 The nitrile group being a good π-acceptor, often helps to design electronic devices. 21 Therefore, synthesis of a diverse range of spiro-heterocycles using malononitrile as a useful tool has attracted chemists far and wide. A number of other strategies have also been employed by different groups using different starting materials, reaction condition and reaction medium.…”
Section: Introductionmentioning
confidence: 99%